Psycho/soma/topografie w polskiej współczesnej poezji kobiet - Morzyńska-Wrzosek, Beata (Acta Neophilologica, 2022)
This article attempts to identify the issues of experiencing the city and its multi-faceted conceptualizations, which are rarely exhibited in research concerning women’s poetry, but often appear in contemporary literature. It offers interpretation of the works of some of the most interesting Polish poets representing various generations (the essay discusses works by Julia Hartwig, Anna Frajlich, and Anna Augustyniak) and worldviews, highlighting specific places and emphasizing the meaning of the senses and emotions in their concretization. It directs attention to the category of experience, examines its constitution and layering progressing in time. It distinguishes particular dimensions – the memory process, the feeling of transience, irreversible loss – and various relationships between them. The analysis, focusing on depicting the sensual and affective experience of urban space, aims to characterize the category of the subject originally included in poetry and illustrates its transformations.